CHEMICAL CHARACTERIZATION OF RAW MATERIALS USED FOR ADSORBENT PRODUCTION - Nomonova, Zilola; Jumayeva, Dilnoza (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This study investigates the initial and post-activation oxide and elemental composition of tar material selected as the raw feedstock for adsorbent production. The research provides a foundation for determining the subsequent stages of chemical activation, including the selection criteria and consumption rates of activating agents. The obtained results offer critical insights into the overall composition of the material and support informed decisions regarding the optimal pathway for further activation processes.